Edukasi Gizi Seimbang Menggunakan Media Permainan Isi Piringku di SD Negeri Pa’bundukang Kabupaten Gowa - Harmawati,; Irwan, Muhammad; Rasmawati, Rasmawati; Rasdiyanah,; Sutria, Eny; Fitriani, Aidah; Adhiwijaya, Ardian; Risnah, (Journal of Community Engagement in Nursing, 2025)
The community service program in the form of balanced nutrition education using the game media contents of my plate was implemented at Pa'bundukang Elementary School, Gowa Regency. The target of the activity was 34 class III students. After consulting with the Paccelekang Community Health Center and coordinating with the Pa; Bundukang Public Elementary School, the activity was carried out on Wednesday, April 24 2025 at 09.30 WITA - finished. The methods used are lectures, discussions and demonstrations involving all participants and activity facilitators. Starting with an opening event, then providing material and finally closing. All participants were very enthusiastic about participating in the entire series of community service activities in a happy atmosphere. So that they understand in simple terms the definition of balanced nutrition as well as the benefits and types of balanced nutrition. It is hoped that this activity will continue by involving families so that they can implement a balanced nutritional menu in everyday life.